The Transportation of the Djehutihotep Statue Revisited - Simon Ayrinhac (Japanese Society of Tribologists, 2016)
The transportation of a colossus painted in the ancient Egyptian tomb of Djehutihotep (Dayr al-Barsha) is known as an example of lubrication application. However the benefits and the nature of lubrication used by ancient Egyptians are controversial. In order to clarify this issue, the physical parameters involved in the transportation are carefully reviewed. The traction force is a key parameter, and is evaluated by simple physical models and the results of biomechanical and ergonomic studies. The results of this work suggest high traction force can be produced only with an excellent team coordination, and the friction coefficient between sledge and ground is efficiently reduced by hypothetical methods which exclude probably wood-on-wood or wood-on-sand surface contacts.